2014
DOI: 10.1002/pip.2570
|View full text |Cite
|
Sign up to set email alerts
|

DC‐sputtered ZnO:Al as transparent conductive oxide for silicon heterojunction solar cells with µc‐Si:H emitter

Abstract: Silicon heterojunction (SHJ) solar cells are highly interesting, because of their high efficiency and low cost fabrication. So far, the most applied transparent conductive oxide (TCO) is indium tin oxide (ITO). The replacement of ITO with cheaper, more abundant and environmental friendly material with texturing capability is a promising way to reduce the production cost of the future SHJ solar cells. Here, we report on the fabrication of the SHJ solar cells with direct current-sputtered aluminum-doped zinc oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…[ 19 ] Another option is to adjust the work function of the p‐a‐Si:H layer by increasing the net doping or applying its microcrystalline structure. [ 20 ] Bivour et al showed that high doping of the p‐a‐Si:H layer was required for the formation of an efficient tunneling junction at the p‐a‐Si:H/ITO contact. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] Another option is to adjust the work function of the p‐a‐Si:H layer by increasing the net doping or applying its microcrystalline structure. [ 20 ] Bivour et al showed that high doping of the p‐a‐Si:H layer was required for the formation of an efficient tunneling junction at the p‐a‐Si:H/ITO contact. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated amorphous silicon (a‐Si:H)/crystalline silicon (c‐Si) heterojunction (HJ) solar cells are the focus of a considerable amount of research because they can achieve high conversion efficiencies with simple fabrication processes . For this type of cell, the highest reported short‐circuit current density ( J sc ), open‐circuit voltage ( V oc ), and fill factor (FF) are 39.5 mA cm −2 , 750 mV, and 0.832, respectively, for a 98‐µm‐thick Czochralski (Cz) c‐Si wafer with a non‐back‐contact structure .…”
Section: Introductionmentioning
confidence: 99%
“…Aluminum doped zinc oxide (ZnO:Al) is used as front or part of the back contact of thin‐film PV technology . Recently, ZnO:Al has been applied successfully to silicon heterojunction solar cells as well . Solar modules and in particular the contact materials must withstand long term outdoor operation.…”
Section: Introductionmentioning
confidence: 99%